2021
DOI: 10.1002/pmrj.12707
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound and shear‐wave elastography characteristics of the iliocapsularis muscle in pincer‐type femoroacetabular impingement

Abstract: Background The iliocapsularis muscle is a structure of the anterior hip, which may play a key role in stabilizing the hip joint, but to our knowledge no studies exist describing ultrasound (US) and shear‐wave characteristics of this muscle. Objectives To investigate the anatomic dimensions and elasticity of the iliocapsularis muscle in patients with pincer‐type femoroacetabular impingement (FAI) and normal hips using gray‐scale US and shear‐wave elastography (SWE). Design Case‐control study. Setting Sports med… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 19 publications
0
9
0
Order By: Relevance
“…Figure 3 displays the reported stiffness values in a body chart. Lower stiffness in the symptomatic group was found in two studies (6.6%) examining the iliotibial band syndrome (Friede et al, 2020) and pincer‐type femoroactebabular impingement (Wang, Cui, et al, 2022). Lower or equal stiffness in the symptomatic group was found in one study (3.3%) that examined also the iliotibial band syndrome (Klauser et al, 2022).…”
Section: Resultsmentioning
confidence: 95%
“…Figure 3 displays the reported stiffness values in a body chart. Lower stiffness in the symptomatic group was found in two studies (6.6%) examining the iliotibial band syndrome (Friede et al, 2020) and pincer‐type femoroactebabular impingement (Wang, Cui, et al, 2022). Lower or equal stiffness in the symptomatic group was found in one study (3.3%) that examined also the iliotibial band syndrome (Klauser et al, 2022).…”
Section: Resultsmentioning
confidence: 95%
“…To further evaluate the ICm prevalence in the human body, one redundant donor data set was excluded in addition to 14 publications, which were either reviews, technical notes, or case studies. A total of 13 studies, published between 1950 and February 14th, 2022, investigated the prevalence of the ICm in a total of 521 anterior human hips (Babst et al, 2011; Baker et al, 2022; Elvan et al, 2019; Fagotti et al, 2020; Haefeli et al, 2015; Konno et al, 2021; Lawrenson et al, 2017; Lawrenson et al, 2020; Philippon et al, 2014; Walters et al, 2014; Wang et al, 2021; Ward et al, 2000; Xu et al, 2021). The ICm was present in 99%, or 518, hips which are in line with a recently published systematic review and meta‐analysis that analyzed dissection results of six studies, reporting a pooled‐prevalence rate of 98.7% (Keet et al, 2021).…”
Section: Resultsmentioning
confidence: 99%
“…These exclusions resulted in 28 PRL articles which included the ICm. Of the 28 publications mentioning the ICm, 19 highlighted the morphology and proposed functional roles of the muscle (Babst et al, 2011;Baker et al, 2022;Das & Singh, 1950;Elvan et al, 2019;Haefeli et al, 2015;Hammoud et al, 2014;Keet et al, 2021;Konno et al, 2021;Lawrenson et al, 2017Lawrenson et al, , 2019Lawrenson et al, , 2020Philippon et al, 2014;Pourcho et al, 2015;Retchford et al, 2013;Ricci & Özçakar, 2019;Saito et al, 2021;Walters et al, 2014;Wang et al, 2021;Ward et al, 2000). Nine additional studies reported the presence of the ICm using clinical scenarios consisting of surgical interventions and diagnostic imaging (Agten et al, 2016;Camenzind et al, 2018;Fagotti et al, 2020;Harris, 2016;Kalhor et al, 2021;Siebenrock et al, 2015;Spiker et al, 2021;Wyatt et al, 2017;Xu et al, 2021).…”
Section: Primary Literature Searchmentioning
confidence: 99%
“…We measured the thickness and shear modulus of the anterior hip joint capsule and muscle thickness, echo intensity, and shear modulus of the IC, iliacus muscle (IL), and rectus femoris (RF). Although the IC is a small and deep muscle, its mechanical properties can still be quantified (Wang et al, 2021). In this study, we measured the shear modulus of the IC, similar to a prior investigation involving healthy participants.…”
Section: Participants and Methodsmentioning
confidence: 99%
“…According to previous studies, the IC is thickened in unstable hip joints with acetabular dysplasia, and the proportion of muscle fat infiltration is lower in the dysplastic hips than in hips with excessive acetabular coverage (Babst et al, 2011; Haefeli et al, 2015). Many studies have investigated changes in the quantity and quality of the IC in patients with hip joint instability and dysplasia (Babst et al, 2011; Haefeli et al, 2015; Wang et al, 2021). In general, as muscle quantity and quality change with aging, eliminating the effects of aging to identify the effects of diseases is necessary.…”
Section: Introductionmentioning
confidence: 99%